PENGARUH EVENT MARKETING, INFLUENCER, DAN FINANCIAL LITERACY TERHADAP KEPUTUSAN PEMBELIAN PRODUK DIAMOND MOBILE LEGENDS: BANG BANG - Ananda, Diva Yulia; Cahya, Septyan Budy (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
This study aims to analyze the influence of event marketing, influencers, and financial literacy on Diamond purchasing decisions in the Mobile Legends game: Bang Bang in Surabaya. The method used is quantitative with survey techniques on 97 active player respondents who have purchased Diamonds. The regression analysis results show that the three variables have a significant effect, both partially and simultaneously, on purchasing decisions. Event marketing creates attraction through the event experience, influencers influence through proximity to the audience, while financial literacy helps players make wiser decisions. These findings are important for digital marketing strategies in the gaming industry.